2021
DOI: 10.1002/eco.2280
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hydropeaking on the attached eggs of a rheophilic cyprinid species

Abstract: Human‐induced changes in the hydrological regimes of lotic waters such as hydropeaking have significant negative impacts on riverine life. However, the impacts of dynamic changes in water flow on adhesive fish eggs are not very well known. We focused on the effects of hydropeaking on the spawning ground of a rheophilic cyprinid fish, the asp (Leuciscus aspius). We tested whether a sudden increase in water velocity caused by hydropeaking may have negative effect on the adhesive eggs by the combination of field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 55 publications
0
26
0
Order By: Relevance
“…This is of particular importance as severe recruitment problems may arise from a combination of stressors such as a poor egg quality, a reduced adhesive ability resulting in higher off‐drift of eggs and deteriorated habitat conditions on spawning grounds. Additionally, recent findings demonstrate that egg adhesiveness at spawning grounds can be extremely reduced in rivers with hydropeaking effects (Bartoň et al., 2021). In turn, improvement of spawning ground quality might partially compensate for reduced egg quality as a loose and porous interstitial as well as low fine sediment infiltration rates positively contribute to hatching success (Nagel et al., 2020a; Nagel et al., 2020a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is of particular importance as severe recruitment problems may arise from a combination of stressors such as a poor egg quality, a reduced adhesive ability resulting in higher off‐drift of eggs and deteriorated habitat conditions on spawning grounds. Additionally, recent findings demonstrate that egg adhesiveness at spawning grounds can be extremely reduced in rivers with hydropeaking effects (Bartoň et al., 2021). In turn, improvement of spawning ground quality might partially compensate for reduced egg quality as a loose and porous interstitial as well as low fine sediment infiltration rates positively contribute to hatching success (Nagel et al., 2020a; Nagel et al., 2020a).…”
Section: Discussionmentioning
confidence: 99%
“…Patzner et al., 2006; Petz‐Glechner et al., 1998; Riehl et al., 2002). This ensures that a large proportion of the eggs laid adhere to surfaces at spawning sites, which in these species are often characterized by medium to rapid current velocities (Bartoň et al., 2021; Melcher & Schmutz, 2010). This is particularly evident in common nase ( Chondrostoma nasus L.) which spawns its eggs at current velocities of up to 1 m/s or even greater (Melcher & Schmutz, 2010; Nagel et al., 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…The 6149 individuals were released in the Želivka Reservoir on 19 May 2020, and the remaining 1426 asp from semi-natural experiment trained on northern pike direct predation were released on 29 July 2020 (7575 individuals in total). The study site has the largest population of asp in the country and is protected by Natura 2000 [7]. The shoreline of Želivka Reservoir was sampled with an electrofishing boat (electrofisher EL 65 II GL DC, Hans Grassel, Schönau am Königsee, Germany, 13 kW, used voltage and current 500 V, 10 A, pulsed DC, frequency 70 × s −1 ) in 24-26 August 2020, on 18 March to 25 April 2021 during the spring spawning migration of asp [48] and on 25-27 August 2021 (Figure 2).…”
Section: Reservoir Stocking Experimentsmentioning
confidence: 99%
“…Populations of many fish species are declining worldwide [1][2][3]. The reasons for declining fish populations are diverse, ranging from habitat alteration to invasions of non-native species [4][5][6][7]. In the freshwater environment, migratory rheophilic fish species are a particularly threatened group [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Declines have been most substantial for the gravel-spawning species of the hyporhitral and epipotamal streams in medium- and large-sized rivers (e.g., grayling Thymallus thymallus, nase Chondrostoma nasus , barbel Barbus barbus ) further aggravated by their much longer generation time over smaller fishes [ 1 ]. The reasons for this decline are many, and to name a few, they are river (habitat) fragmentation [ 4 ], the effects of increasing temperature, and increasing fine sediments [ 5 ] or altered river flow and hydropeaking [ 6 ]. In central European rivers, Mueller et al [ 1 ] identified fish species that deserve higher priority in conservation management, and half of them are large potamodromous rheophilic cyprinids.…”
Section: Introductionmentioning
confidence: 99%